ANALISA PENDAPATAN PETANI KARET DARI HUTAN TANAMAN RAKYAT DI TRANS SP 1 DESA PANGMILANG KECAMATAN SINGKAWANG SELATAN KOTA SINGKAWANG KALIMANTAN BARAT - Miranda, Azelia; Lumangkun, Augustine; Husni, Harnani (JURNAL HUTAN LESTARI, 2015)
Rubber plantation in the forest area managed by local people is one of their income source. They depend a lot on these rubber trees for their life. The rubber plant is one of the important commodity and has a very large role in the economy sector. Most of the people transmigration of ressetlement unit 1 in Pangmilang Village Singkawang Selatan Subdistrict West Borneo have rubber plantation in forest area. They work as rubber tappers and farmers. The research purpose is to know the income level and factors that influence income level of farmers from rubber in forest plantation area. These factors are : land area (X1), the quantity of trees tapped (X2), the man power of working time (X3), as well as the length of time worked as rubber farmers (X4). The research method used survey technique with descriptive analysis. The results showed that the rubber revenue obtained Rp 1.072.980,--/month. The contribution of this rubber is 39,83% (Rp 1.072.980,--) from total revenue of Rp 2.694.113,--. Four variables have significant effect on the income to the value in which Fhit = 3,45 > F(0,05;4-1)= 2,579 on the level analysis of 95%. Keywords : Forest plantation community, income analysis, rubber, Singkawang City, survey method.